2020
DOI: 10.1093/jxb/eraa327
|View full text |Cite
|
Sign up to set email alerts
|

A blueberry MIR156a–SPL12 module coordinates the accumulation of chlorophylls and anthocyanins during fruit ripening

Abstract: Color change is an important event during fruit maturation in blueberry, usually depending on chlorophyll degradation and anthocyanin accumulation. miR156/SPL modules are an important group of regulatory hubs involved in the regulation of anthocyanin biosynthesis. However, little is known regarding the roles of miR156/SPLs in blueberry and chlorophyll metabolism during color change. In this study, a MIR156 gene (VcMIR156a) was experimentally identified in blueberry. Overexpression of VcMIR156a in tomato enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 69 publications
1
39
0
Order By: Relevance
“…Northland) from clonal propagation were grown at the experimental station at Jilin University (Changchun, China). Blueberry tissues were randomly harvested from six different seven-year-old blueberry plants, including new leaf, young shoot, unopened flower, opening flower, and fruit at six developmental stages [green pad (FS1), green cup I (FS2), green cup II (FS3), light green/white (FWS), pink (FPS) and blue (FMS) fruits] ( Li et al, 2020 ), frozen in liquid nitrogen and stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Northland) from clonal propagation were grown at the experimental station at Jilin University (Changchun, China). Blueberry tissues were randomly harvested from six different seven-year-old blueberry plants, including new leaf, young shoot, unopened flower, opening flower, and fruit at six developmental stages [green pad (FS1), green cup I (FS2), green cup II (FS3), light green/white (FWS), pink (FPS) and blue (FMS) fruits] ( Li et al, 2020 ), frozen in liquid nitrogen and stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…The VcMIR156a gene was constructed into pBI121 as described previously ( Li et al, 2020 ) and transferred into Agrobacterium tumefaciens strain EHA105. Blueberry transformation was performed according to the method described by Song and Sink (2006) .…”
Section: Methodsmentioning
confidence: 99%
“…Blueberry ( Vaccinium spp. ), one of major genera in the tribe Vacciniae of the Ericaceae, produces a small false berry with high levels of bioactive metabolites, that have been discovered to be beneficial to human health, with antioxidant, anti-inflammatory, anticarcinogenic, antiobesity properties, and neuroprotective activities [ 18 , 19 ]. However, blueberry fruit is smaller than most domesticated fruit, such as tomato, kiwifruit, and grape, whereas the systematic anatomical and molecular regulatory mechanisms of fruit size/weight remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…However, we found that some members of miR395 family, miR167 family and Phn-m0170-3p were signi cantly up-regulated in the leaves and phn-m0170-3p may be involved in the regulation of 16 coding genes. miR156e and miR156l were speci cally up-regulated in stem, may affect the expression of the target gene SPL, prolong the time of vegetative growth, delay the owering, regulate the plant architecture, and affect the formation of anthocyanins in the stem of P. heterophylla [38]. It is worth noting that Phn−m0082−3p is speci cally expressed in the stem and may regulate the expression of 36 coding genes, and its function needs further study.…”
Section: Discussionmentioning
confidence: 96%
“…This result indicated that down-regulated expression of miR166 in the tuberous root of P. heterophylla can promote the up-regulated expression of homeodomain leucine zipper (HD-Zip III) genes, affect the development process of leaf polarity establishment and vascular tissue differentiation, and which suggested that miR166 family and its target gene (HD-Zip III) may also play an important role in development of tuberous root. Some members of ARF family were targeted by miR160, such as ARF 10, ARF 16 and ARF 17. miR160 has showed extreme importance in differentiation of root cap cells, morphogenesis of embryo and leaf, development of ower [34][35][36][37][38][39][40][41][42][43][44][45][46], and mainly regulated the expression of its targets genes (AFR). 12 novel miRNAs were signi cantly upregulated in the xylem of tuberous root and 24 unigenes were targeted by Phn-m0101-5p, which suggested its important role in the development of root xylem.…”
Section: Discussionmentioning
confidence: 99%